A meso-scale model to predict flow stress and microstructure during hot deformation of IN718WP - Kumar N.; Ferraz F.M.B.; Buzolin R.H.; Shahryari E.; Poletti M.C.; Yadav S.D. (My University, 2025)
This research presents a dislocation-based hot deformation model to address a nickel-based superalloy's flow stress response and discontinuous dynamic recrystallization (DDRX) behavior. The developed model can predict the flow curves and subsequent microstructure evolutions during the hot deformation. The evolution of microstructure-reliant internal variables was predicted and validated thoroughly. Furthermore, the influence of strain rate and temperature on the glide and climb velocities have also been discussed to reveal more insights into the microstructural development. Dislocation density and DDRX fraction predicted from the model was compared with dislocation density and DDRX fraction obtained from electron backscattered diffraction (EBSD) measurements with reasonable matching. Higher temperatures and slower strain rates provide favorable conditions for DDRX in this alloy. The importance of this model relies on its prediction capability in terms of flow curve, mobile and immobile dislocation densities, DDRX fraction, grain size and dislocation velocities. Single set of parameters were obtained from twelve experimental curves and rest of the eleven curves were predicted by the model using those parameters. The present research approach is helpful to predict the multiple flow curves along with the corresponding microstructure evolution in LSFE materials. © 2025 Elsevier Ltd